In vivo tracking of bioorthogonally labeled T-cells for predicting therapeutic efficacy of adoptive T-cell therapy - Kim, Woojun; Yoon, Hong Yeol; Lim, Seungho; Stayton, Patrick S.; Kim, In-San; Kim, Kwangmeyung; Kwon, Ick Chan (ELSEVIER, 2021)
Non-invasive tracking of T-cells may help to predict the patient responsiveness and therapeutic outcome. Herein, we developed bioorthogonal T-cell labeling and tracking strategy using bioorthogonal click chemistry. First, ovalbumin (OVA) antigen-specific cytotoxic T-cells (CTLs) were incubated with N-azidoacetyl-D-mannosamine-tetraacylated (Ac(4)ManNAz) for incorporating azide (-N-3) groups on the surface of CTLs via metabolic glyco-engineering. Subsequently, azide groups on the CTLs were chemically labeled with near infrared fluorescence (NIRF) dye, Cy5.5, conjugated dibenzylcyclooctyne (DBCO-Cy5.5) via bioorthogonal click chemistry, resulting in Cy5.5-labeled CTLs (Cy5.5-CTLs). The labeling efficiency of Cy5.5-CTLs could be readily controlled by changing concentrations of Ac(4)ManNAz and DBCO-Cy5.5 in cultured cells. Importantly, Cy5.5-CTLs presented the strong NIRF signals in vitro and they showed no significant changes in the functional properties, such as cell viability, proliferation, and antigen-specific cytolytic activity. In ovalbumin (OVA)-expressing E.G-7 tumor-bearing immune-deficient mice, intravenously injected Cy5.5-CTLs were clearly observed at targeted solid tumors via non-invasive NIRF imaging. Moreover, tumor growth inhibition of E.G-7 tumors was closely correlated with the intensity of NIRF signals from Cy5.5-CTLs at tumors after 2-3 days post-injection. The Cy5.5-CTLs showed different therapeutic responses in E.G-7 tumor-bearing immune-competent mice, in which they were divided by their tumor growth efficacy as 'high therapeutic response (TR (+))' and 'low therapeutic response (TR (-))'. These different therapeutic responses of Cy5.5-CTLs were highly correlated with the NIRF signals of Cy5.5-CTLs at targeted tumor tissues in the early stage. Therefore, non-invasive tracking of T-cells can be able to predict and elicit therapeutic responses in the adoptive T-cell therapy.